UPAYA PENCEGAHAN PENYAKIT GERD MELALUI PEMBERIAN PENYULUHAN KESEHATAN - Helsy Desvitasari (IKesT Muhammadiyah Palembang, 2022)
GERD or Gastroesophageal Reflux Disease (GERD) is a chronic disease of the digestive system, where the reflux of gastric contents into the esophagus can cause inflammation. The current phenoma is that there are many fast food and various flavors that are sold both offline and online. Food menus with spicy compounds dominate the gelumbang market. This is also a trigger for gastric problems experienced by the Gelumbang community, especially among educators. Through the provision of counseling as a form of disease prevention in order to increase understanding of healthy food consumption patterns that do not trigger excess gastric acid production. This service activity aims to provide information and improve teachers' understanding of GERD. Outreach activities in the school environment using posters and leaflets as media. The results of the activity show that all teachers understand about GERD. It is hoped that the outreach activities can create a culture of implementing healthy lifestyles in the school environment and at home.